Model Reference Adaptive Control for Single Phase Buck Boost Inverter - Purwadi Agus Darwito; Mega Arintika Yuliana (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2022)
An inverter is a device that converts DC voltage into AC voltage. AC output voltage is usually expected to be fixed and symmetrical at certain amplitudes and frequencies. Most inverters use a pulse width modulation circuit to regulate the output voltage. There are many topologies in building inverter circuits. In this research, the BuckBost topology is used to meet the output voltage greater or smaller than the input voltage. In this research, a Buck-Boost inverter is designed to convert a 12 volts DC input voltage to a 220 volts AC output voltage. In addition to the magnitude, the output voltage must also be considered of quality, in the sense that if there is a ripple, it should be as small as possible. For this purposed MRAC control is used, and simulated using Matlab. The test results with simulation show that the response of the SPBBI system with the MRAC controller with the MIT rule method can achieve the expected output voltage of 220V at the reference frequency of 49.95 Hz, 50 Hz, 50.05 Hz, and 60 Hz. System response is very dependent on the value of the adaptation gain. The adaptation gain that produces the best system response is 0.000001 with a settling time of 0.095 seconds.